Effect of GammaRay in the Progeny of Trispecific Hybrid [(Gossypium hirsutum x G. raimondii)² x G. sturtianum] - Fatimata Bintou Hassedine DIOUF; Halima BENBOUZA; N’Guessan Olivier KONAN; Djibril SARR; Khadidiatou Ndoye NDIR; Jean Pierre BAUDOIN; Guy MERGEAI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2010)
The objective of this study is to analyse the possibilities of fixing in the progeny of the [(Gossypium hirsutum x G. raimondii)² x G. sturtianum] (HRS) trispecies hybrid, the glandless-seed and glanded-plant trait. The expression of the character was analysed in progenies obtained by selfing the HRS BC2S5/9/6/1/51/15 genetic stock. This character is controlled by one or more genes located on introgressed chromosome fragments of G. sturtianum. These foreign DNA fragments seem also carriers of gametes terminators genes on the same chromosome fragments and there would be a possible existence of negative interactions between some of the introgressed G. sturtianum alleles and the G. hirsutum genetic background inducing post-zygotic mortality. In order to break existing lethal links, some of the studied seeds were treated with 15 krad of gamma radiation. The transfer of G. sturtianum chromosome fragments introgressed stocks was assessed using ten mapped SSR markers, carried out on 78 plants HRS ‘BC2S6’. Gamma irradiation used to overcome lethality in HRS hybrid did not give expected results in M2 because of high rate of abortion observed in HRS ‘BC2S6’ seeds. However, gamma ray did not induce the appearance of chimeric tissues in the HRS ‘BC2S5/9/6/1/51/15’ in M1 plants. Moreover, the notable fertility improvement observed for some plants issued from irradiated seeds constitutes a clue of the achievement of favourables recombinations due to the gamma ray treatment. The perspectives opened by the results obtained for the stabilization of the glandless-seed and glanded-plant trait in a G. hirsutum commercial variety are discussed.